2003
DOI: 10.1002/ana.10464
|View full text |Cite
|
Sign up to set email alerts
|

Familial hemiplegic migraine type 2 is linked to 0.9Mb region on chromosome 1q23

Abstract: Familial hemiplegic migraine (FHM) is a rare autosomal dominant disorder characterized by episodes of transient hemiparesis followed by headache. Two chromosomal loci are associated to FHM: FHM1 on chromosome 19 and FHM2 on chromosome 1q21-23. Mutations of the alpha-1A subunit of the voltage gated calcium channel (CACNA1A) are responsible for FHM1. FHM2 critical region spans 28 cM, hence hampering the identification of the responsible gene. Here, we report the FHM2 locus refining by linkage analysis on two lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 24 publications
2
65
1
Order By: Relevance
“…Roughly half of the FHM families have been linked to chromosome 19p13 (Joutel et Miguel Estevez · Kathy L. Gardner al. 1993), and analysis of other FHM families has shown evidence for linkage among 20%-30% of families to 1q21-23 (Ducros et al 1997;Gardner et al 2000;Marconi et al 2003). Additional FHM families not linked to chromosome 1q or 19p13 have also been reported (Ducros et al 1997).…”
Section: Introductionmentioning
confidence: 90%
“…Roughly half of the FHM families have been linked to chromosome 19p13 (Joutel et Miguel Estevez · Kathy L. Gardner al. 1993), and analysis of other FHM families has shown evidence for linkage among 20%-30% of families to 1q21-23 (Ducros et al 1997;Gardner et al 2000;Marconi et al 2003). Additional FHM families not linked to chromosome 1q or 19p13 have also been reported (Ducros et al 1997).…”
Section: Introductionmentioning
confidence: 90%
“…In four families with ATP1A2 mutations, age of onset has ranged from 2 to 15 years, and in one, benign infantile convulsions of infancy cosegregated with the phenotype. [7][8][9] The wide range of age of onset, the seizures observed in a subset of affected subjects, and the similar phenomenology of the movement disorder in FHM and AHC prompted us to evaluate a group of familial and sporadic AHC cases for mutations in the ATP1A2 gene. Here, we present clinical and molecular data from a Greek kindred with a novel ATP1A2 gene mutation and document exclusion of ATP1A2 mutations as a common cause of classic sporadic or familial forms of AHC.…”
mentioning
confidence: 99%
“…However, as noted by Terwindt et al [19], this mutation did not occur in all of the families. Subsequent chromosomal mapping and linkage analysis identified an additional locus on chromosome 1q31 [22] and chromosome 1q23 [23]. In 2003, Marconi et al [23] identified that the gene affected was the 2 subunit of the Na+/K+ pump (ATP1A2).…”
Section: Familial Hemiplegic Migraine-atp1a2mentioning
confidence: 98%
“…Subsequent chromosomal mapping and linkage analysis identified an additional locus on chromosome 1q31 [22] and chromosome 1q23 [23]. In 2003, Marconi et al [23] identified that the gene affected was the 2 subunit of the Na+/K+ pump (ATP1A2). The product of this gene was localized not at the synapse but rather in the astrocytes surrounding the nerve endings and connecting to the blood vessels.…”
Section: Familial Hemiplegic Migraine-atp1a2mentioning
confidence: 98%